Fully Vertical GaN-on-SiC p-i-n Diodes With BFOM of 2.89 GW/cm2 - Jialun Li; Renqiang Zhu; Ka Ming Wong; Kei May Lau (IEEE Journal of the Electron Devices Society)
This letter reports a high-performance fully-vertical GaN-on-SiC p-i-n diode enabled by a conductive n-AlGaN buffer. The buffer conductivity was optimized by tuning the Al composition. The diode presents an ultra-low specific ON-resistance of 0.25 $\text{m}Ω · $ cm2, a high current swing of 1011, and a high breakdown voltage of 850 V with a 5- $μ \text{m}$ -thick drift layer, leading to a Baliga’s figure of merit (BFOM) of 2.89 GW/cm2. The diode performance at elevated temperatures and the OFF-state leakage mechanism are analyzed. The demonstrated fully-vertical GaN-on-SiC p-i-n diode with a conductive buffer reveals a simple way towards realizing high-performance fully-vertical GaN-on-SiC devices for high power applications.